PERAN POLA ASUH DALAM PEMBENTUKAN MINAT BELAJAR ANAK DI DESA MEDINI - yuliana sulistyaningrum putri; ika ari pratiwi; erik aditia ismaya (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
This study aims to determine the form of parenting applied by parents to children’s interest in learning in the village of medini.this study used a descriptive quantitative approach in presenting the research data. The data collection process is carried out using observation, interview, documentation and recording methods. The results showed that in providing a form of parenting in Medini village using a democratic form of parenting. The form of democratic parenting by applying learning discipline, being independent and practicing worship as well as actions that reflect character can play a role for children, especially in terms of children’s learning interest. The parenting style applied by the child’s parents is able to provide encouragement for children’s interest in learning in the family environment so that the child is able to get good learning outcomes. Not only that, the form of democratic parenting is also able to shape the character in children in the form of discipline, independence, religion, and communication. As for the suggestions in this study for children so that children can have good interest in learning.